Incidence and Characteristics of Humeral Shaft Fractures After Subpectoral Biceps Tenodesis. Issue 3 (28th March 2019) - Overmann, Archie L.; Colantonio, Donald F.; Wheatley, Benjamin M.; Volk, William R.; Kilcoyne, Kelly G.; Dickens, Jonathan F.
Background: Biceps tenodesis is a procedure that can address biceps and labral pathology. While there is an increased risk of humeral fracture after biceps tenodesis, it has been described only in case reports. Purpose: To identify the incidence, demographics, and characteristics of humeral shaft fractures after biceps tenodesis. Study Design: Case series; Level of evidence, 4. Methods: The US Military Health System Data Repository was searched for patients with a Current Procedural Terminology code for biceps tenodesis between January 2013 and December 2016. The cohort of identified patients was then searched for those assigned a code for humeral fracture per the International Classification of Diseases, 9th Revision and 10th Revision. The electronic health records and radiographs of patients who were diagnosed with a humeral fracture were then evaluated to confirm that the fracture was related to the biceps tenodesis. Records were then reviewed for patient demographics, radiographs, operative reports, and clinical notes. Results: A total of 15, 085 biceps tenodeses were performed between January 2013 and December 2016. There were 11 postoperative and 1 intraoperative humeral fractures. The incidence of fracture was <0.1%. All fractures were extra-articular spiral fractures that propagated through the tenodesis site. Eight patients were treated with functional bracing, 3 with open reduction and internal fixation, and 1 with a soft tissue biceps tenodesis revision. Of 8 patients successfully treated nonoperatively, 6 regained full range of shoulder motion. Only 2 of the 4 patients who required operative treatment regained full range of shoulder motion. Conclusion: Humeral shaft fracture after biceps tenodesis is a rare complication that occurs in 7.9 out of 10, 000 cases. Fractures occurred after various methods of fixation, including suture anchor, cortical button, and interference screw. Most patients were initially treated nonoperatively, and those who healed usually achieved full range of motion; however, those who required operative intervention often had restricted range of motion on final follow-up. Future studies should determine risk factors for fracture after biceps tenodesis.